ACCOUNTING AS AN INFORMATION BASIS FOR ENSURING THE ECONOMIC SECURITY OF ENTERPRISES - IVANOV, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to exploring the accounting system's role in ensuring an enterprise's economic security. The study's relevance is determined by the dynamic nature of the economic environment, where enterprises face risks, competition, and instability, which negatively affect their economic security. The purpose of the article is to substantiate the accounting system's role in ensuring an enterprise's economic security from the perspective of forming an informational basis for managerial decision-making, as well as to develop recommendations for establishing an enterprise's accounting system.The article analyzes the dynamics of the performance of Ukrainian enterprises from 2013 to 2022 and, based on key trends, characterizes the state of economic security of enterprises. Various approaches to defining the concept of economic security of enterprises are considered, and its essence is determined. The role of accounting in ensuring the economic security of an enterprise is revealed, and the main functions it should perform are highlighted.It is established that accounting forms the foundation of informational support for managing economic security and making managerial decisions. The primary requirements for an accounting system to ensure an enterprise's economic security are outlined. One of the main tasks of organizing accounting to form informational support for managing economic security is determining the enterprise's resources and their key indicators for further analysis, monitoring, and managerial decision-making.A list of resources for which information collection should be conducted is proposed, along with indicators for analysis of economic security that the accounting system should generate. It is emphasized that, for managing economic security, the accounting system must provide both financial and non-financial information. It is demonstrated that the accounting system must combine financial and management accounting to effectively manage economic security.The study's results can be applied in enterprises' practical activities when organizing their accounting systems to manage economic security.
Keywords: accounting; economic security; information; control; resources; financial accounting; management accounting